Photo-anthropometric Study of Nasal Length among Tribal Garo and Non-tribal Adult Bangladeshi Female of Greater Mymensingh Districts - Tania, Israt Jahan; Naushaba, Humaira; Paul, Uttam Kumar; Akhter, Mahbuba; Khan, Farzana Islam; Morium, Umma (Bangladesh Journal of Anatomy, 2017)
Background: The nose is a person’s most defining feature because it is at the center of the face. The shape and length of the nose differs from race to race, tribe to tribe and from one environment to another. Anthropometry is a series of systematized measuring techniques that expresses quantitatively the dimensions of human body and skeleton which play an important role in distinguishing race. It provides quantitative data in identifying people having different physical characteristics in diagnosing people having craniofacial abnormality and to compare between patient and normal population. Materials & Methods: Cross sectional analytical type of study was conducted in the department of Anatomy, Sir Salimullah Medical College, Dhaka, from January 2015 to December 2015.The study subjects consist of two hundred (200) adult Bangladeshi female of greater Mymensingh districts of which 100 were Garo tribal female and 100 were non-tribal female. Results: The mean (±SD) nasal length from ‘nasion to subnasale’ was higher in non- tribal female than Garo tribal female and was statistically significant (p<0.001). Conclusion: Nasal length from ‘nasion to subnasale’ was higher in non- tribal female compared to Garo tribal female. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 1, pp. 15-18